2000
DOI: 10.1063/1.1290733
|View full text |Cite
|
Sign up to set email alerts
|

Thomson scattering in a low-pressure argon mercury positive column

Abstract: The electron density and the electron temperature in a low-pressure argon mercury positive column are determined using Thomson scattering. Special attention has been given to the stray light reduction in the Thomson scattering setup. The results are obtained in a discharge tube with a 26 mm diam, 5 mbar of argon, a mercury pressure in between 0.14 and 1.7 Pa, and an electric current ranging from 200 to 400 mA. The systematic error in the electron density is 15%, the statistical error is 25%. The total error in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…Bakker and Kroesen have recently demonstrated that color temperature in fluorescent lamps can be modified by controlling radial cataphoresis. 24,25 Numerical modeling of low-pressure gas discharges is a well-developed field that relies heavily on basic atomic data. For Ba, there is a need for a large volume of data including radiative decay rates, electron-impact excitation, and ionization cross sections of Ba, Ba*-Ba quenching cross sections, Ba*-rare gas quenching cross sections, line broadening coefficients, and diffusion coefficients.…”
Section: Modelmentioning
confidence: 99%
“…Bakker and Kroesen have recently demonstrated that color temperature in fluorescent lamps can be modified by controlling radial cataphoresis. 24,25 Numerical modeling of low-pressure gas discharges is a well-developed field that relies heavily on basic atomic data. For Ba, there is a need for a large volume of data including radiative decay rates, electron-impact excitation, and ionization cross sections of Ba, Ba*-Ba quenching cross sections, Ba*-rare gas quenching cross sections, line broadening coefficients, and diffusion coefficients.…”
Section: Modelmentioning
confidence: 99%
“…8 and the density of the 2p states as given in Ref. 7, we can conclude that the LIF signal is of the same order of magnitude as the Thomson scattering signal for the measurements in series A and B. For series C, the LIF signal is much lower, and for series D and E, the LIF signal is negligible.…”
Section: Resultsmentioning
confidence: 60%
“…The error in the absolute value of the electron density due to uncertainty in the calibration is approximately 15%. 9 For the measurements at the two lowest mercury pressures, there is an additional systematic error introduced by the correction for the LIF signal. For the 18°C measurements, this additional error is at maximum 30%, for the 24°C, this additional error is at maximum 10%.…”
Section: A Electron Densitymentioning
confidence: 99%
See 2 more Smart Citations